Biochemical confirmation and characterization of the family-57-like alpha-amylase of Methanococcus jannaschii - Kim, J W; Flowers, L O; Whiteley, M; Peeples, T L (Folia microbiologica, 2001)
The gene encoding a family-57-like alpha-amylase in the hyperthermophilic archaeon Methanococcus jannaschii, has been cloned into Escherichia coli. Extremely thermoactive alpha-amylase was confirmed in partially purified enzyme solution of the recombinant culture. This enzyme activity had a temperature optimum of 120 degrees C and a pH optimum 5.0-8.0. The amylase activity is extremely stable against denaturants. Hydrolysis of large sugar polymers with alpha-1-6 and alpha-1-4 linkages yields products including glucose polymers of 1-7 units. Highest activity is exhibited on amylose. The catalyst exhibited a half-life of 50 h at 100 degrees C, among the highest reported thermostabilities of natural amylases.
Keywords: Methanococcus; Escherichia coli; Glucans; sekvenční seřazení; rekombinantní proteiny; alpha-Amylases; Amylose; Hydrogen-Ion Concentration; Cloning, Molecular; Carbohydrate Metabolism; Molecular Sequence Data; sekvence aminokyselin; alfa-amylasy; amylosa; molekulární sekvence - údaje; glukany; Recombinant Proteins; metabolismus sacharidů; koncentrace vodíkových iontů; klonování DNA; Sequence Alignment; Temperature; teplota; Amino Acid Sequence